Scaling up the shape: a novel growth pattern of gallium clusters - Kaware, Vaibhav; Joshi, Kavita (Journal of Chemical Physics, 2014)
Putative global minima for Ga+N clusters with size ``N'' ranging from 49 to 70 are found by employing the Kohn-Sham formulation of the density functional theory, and their evolution is described and discussed in detail. We have discovered a unique growth pattern in these clusters, all of which are hollow core-shell structures. They evolve with size from one spherical core-shell to the next spherical core-shell structure mediated by prolate geometries, with an increase in overall diameter of the core, as well as the shell, without putting on new layers of atoms. We also present a complete picture of bonding in gallium clusters by critically analyzing the molecular orbitals, the electron localization function, and Bader charges. Bonding in these clusters is a mixture of metallic and covalent type that leans towards covalency, accompanied by marginal charge transfer from the surface to the core. Most molecular orbitals of Ga clusters are non-jellium type. Covalency of bonding is supported by a wide localization window of electron localization function, and joining of its basins along the bonds. (C) 2014 AIP Publishing LLC.

Single-atom alloys of Cu(211) with earth-abundant metals for enhanced activity towards CO2 dissociation - Thakkar, Kavita; Joshi, Kavita (Journal of Molecular Graphics and Modelling, 2024)
CO2, a byproduct from various industrial reactions, must not be released into the atmosphere and should be managed through capture, conversion, and utilization. The first step in converting CO2 into valuable products is to break the C-O bond. This work focuses on designing Single Atom Catalysts (SACs) by doping Cu(211) surface with 13 different s, p, and d block elements with an aim to minimize the activation barrier for C-O bond cleavage. Our work demonstrates that SACs of Mg/Al/Pt@Cu(211) favor CO2 chemisorption compared to Cu(211) where CO2 physisorbs. The barrier for CO2 dissociation is lowest for Mg@Cu(211) and it increases in the order Mg@Cu(211) < Al@Cu(211) < Pt@Cu(211) < Zn@Cu(211) < Ga@Cu(211) < Cu@Cu(211) < Pd@Cu(211). These findings suggest that doping Cu(211) with earth-abundant metal like Mg can potentially be a viable catalyst for CO2 conversion, providing a promising solution to reduce carbon footprint and mitigate climate change.
Keywords: CO2; Cu(211); DFT; Single atom catalysts

Solid state hydrogen storage: Decoding the path through machine learning - Verma, Ashwini; Wilson, Nikhil; Joshi, Kavita (International Journal of Hydrogen Energy, 2024)
We present a machine learning (ML) framework HEART (HydrogEn storAge propeRty predicTor) for identifying suitable families of metal alloys for hydrogen storage under ambient conditions. Our framework includes two ML models that predict the hydrogen storage capacity (HYST) and the enthalpy of hydride formation (THOR) of multi-component metal alloys. We demonstrate that a chemically diverse set of features effectively describes the hydrogen storage properties of the alloys. In HYST, we use absorption temperature as a feature which improved H2wt% prediction significantly. For out-of-the-bag samples, HYST predicted H2wt% with R2 score of 0.81 and mean absolute error (MAE) of 0.45 wt% whereas R2 score is 0.89 and MAE is 4.53 kJ/molH2 for THOR. These models are further employed to predict H2wt% and Delta H for similar to 6.4 million multi-component metal alloys. We have identified 6480 compositions with superior storage properties (H2wt% > 2.5 at room temperature and Delta H < 60 kJ/molH2). We have also discussed in detail the interesting trends picked up by these models like temperature dependent variation in the rate of hydrogenation and alloying effect on H2wt% and Delta H in different families of alloys. Importantly certain elements like Al, Si, Sc, Cr, and Mn when mixed in small fractions with hydriding elements like Mg, Ti, V etc. systematically reduce Delta H without significantly compromising the storage capacity. Further upon increasing the number of elements in the alloy i.e from binary to ternary to quaternary, the number of compositions with lower enthalpies also increases. From the 6.4 million compositions, we have reported new alloy families having potential for hydrogen storage at room temperature. Finally, we demonstrate that HEART has the potential to scan vast chemical spaces by narrowing down potential materials for hydrogen storage.
Keywords: Enthalpy of hydride formation; Hydrogen storage capacity; Metal hydrides; Predictive machine learning models; Solid-state hydrogen storage

Sequential nitro-michael addition and reductive cyclization cascade reaction for diastereoselective synthesis of multifunctionalized 3,3′-pyrrolidinyl-spirooxindoles - Nichinde, Chandrakant B.; Bhati, Meema; Girase, Amardipsing S.; Patil, Baliram R.; Chaudhari, Suryakant S.; Gamidi, Rama Krishna; Joshi, Kavita; Kinage, Anil K. (European Journal of Organic Chemistry, 2025)
In this investigation, we elucidated, one-pot two stage efficient synthesis of multifuctionalized spiro[oxindole -3,3 `-pyrrolidine]. The methodology proceeds via organocatalyzed nitro-Michael addition reaction between indolylidenecyanoesters and nitroalkanes to formed nitro-Michael adduct which transformed into multifunctionalized 3,3 `-pyrrolidinyl-spirooxindoles by metal catalyzed reductive cyclization cascade. DFT investigations were conducted to elucidate the mechanism underlying the preferential reduction of the nitro group, with subsequent attack on the nitrile and ester groups remain inert throughout the reaction process. The approach is operationally simple, easily scalable, exhibits compatibility with readily accessible starting material and catalysts, thereby emphasizing cost-effectiveness.
Keywords: 3 `-pyrrolidinyl spirooxindoles; DFT study for regioselective cyclization; Diastereoselective 3; organocatalysis; Pd/C catalysed partial reductive spirocyclization